Municipal Solid Waste Segregation: A Behavioural Perspective - Singh, Manmohan (My University, 2024)
In developing countries, the collection and disposal of Municipal Solid Waste without segregation is a wicked problem concerning Municipal Solid Waste Management, leading to environmental pollution. The major reasons for the prevailing MSWM scenario in India are unsegregated Municipal Solid Waste at the source of its generation i.e., households, citizens’ attitudes, an unorganized informal trash sector, ill-prepared fiscal policies, and ineffective government policies. The government, policy makers, urban-local bodies, and households are highly concerned about this issue. Further, the literature spotlights the significance of the role of household and individuals’ cognition in shaping their environmental behaviour and hence the environmental behaviour of the public, at large. The scholars have called for research to gain in-depth insights into individuals’ cognitive factors, principally the impact of their personal values, attitude in shaping their behaviour towards environmental issues in the context of a household. Understanding of cognitive factors regarding community waste segregation behaviour can help decipher the underlying causes for developing appropriate action programmes to bring a desired change in the behaviour of individuals generating the MSW. This study is a detailed analysis of the cognitive factors affecting MSW segregation at the household level and suggests possible solutions for policy makers and urban local bodies, like municipal corporations. Hence, to have a thorough knowledge of the subject and to bridge the research gaps, this research empirically investigates the relationships between individuals’ values, attitude, and behaviour towards Municipal Solid Waste initiatives, like collection, its segregation and dumping at the landfill sites, in the cities and townships in the State of Punjab (India), by employing the Value Attitude Behavioural theory, as a theoretical background. For undertaking the same, the data was collected from the residents living in the cities and towns of state of Punjab, to examine their attitude and behaviour regarding Municipal Solid Waste segregation at source. This study establishes that values of individuals have significant impact upon their attitude, different type of values put impact upon attitude differently. Self-Transcendence Value (Benevolence) has positive influence upon Municipal Solid Waste segregation behaviour, on the other hand Self Enhancement Value (Power) is found to be having negative impact upon waste segregation behaviour. Similarly, an individual having Self Transcendent Value (Benevolence) carries a positive attitude towards environmental concerns, person having Self Enhancement Value (Power) has a negative approach towards pro-environmental behaviour. It has further been observed, in our findings, that the attitude of an individual acts and mediates between his values and behaviour. It is also found in the present study that gender as a demographic variable of individuals, be a male or female, has an insignificant impact upon Municipal Solid Waste segregation behaviour. Based on the findings, the study presents different implications for several stakeholders. Firstly, this study illustrates the significance of individuals' personal values in influencing their attitude towards waste segregation. Second, the study extends the conceptual foundations in the realm of study, and as per best of our knowledge, this is the first ever endeavour to apply Value–Attitude-Behaviour theory, in understanding the behaviour of individuals at the household level, towards MSW segregation. As far as the theoretical contribution of the study is concerned, this research broadens the scope of existing literature by investigating the value, attitude and behaviour relationship and the impact thereof upon Municipal Solid Waste segregation. This study and its results have a thought-provoking benefit for policymakers to inculcate its results, which have never been part of the previous rules, regulations, and policy guidelines, so far. A lot of benefits can be derived by the practitioners, major stakeholders i.e., urban local bodies, state governments and executing agencies, specifically those who undertake such projects upon Public Private Partnership mode. The study also presents future research directions.
Keywords: Attitudes, Behaviour; Municipal Solid Waste, Municipal Solid Waste Management, Waste Segregation, Urban Local Bodies, Values; Value-Attitude-Behaviour Theory; Environment